2019
DOI: 10.3389/fphar.2019.01065
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Pharmacological Mechanisms of the Huayu-Qiangshen-Tongbi Formula Through Integrating Network Pharmacology and In Vitro Pharmacological Investigation

Abstract: Rheumatoid arthritis is a chronic inflammatory autoimmune disease, causing articular and extra-articular dysfunctions among patients, and it could result in irreversible joint damages or disability if untreated. A traditional Chinese medicine formula, Huayu-Qiangshen-Tongbi (HT) formula, has been observed successful in controlling rheumatoid arthritis progression in traditional Chinese medicine clinics. In this study, we conducted a systematic analysis of the HT formula with a purpose of proposing for its pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…According to our previous results from computational predictions, RA was frequently involved in multiple signal pathways ( Wang et al, 2019 ). The interactions of these pathways were associated with pathological mechanisms of RA.…”
Section: Discussionmentioning
confidence: 75%
“…According to our previous results from computational predictions, RA was frequently involved in multiple signal pathways ( Wang et al, 2019 ). The interactions of these pathways were associated with pathological mechanisms of RA.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have shown that herbal medicine monotherapy or combination therapy has efficacy in relieving clinical symptoms, signs, and indicators of inflammatory activity for RA patients ( 12 , 32 ). According to previous pharmacological studies, the herbals in HQT formula are proven to have a variety of pharmacological effects, such as anti-inflammatory properties, analgesia, and immune suppression ( 33 , 34 ), supporting the clinical efficacy of HQT in RA treatment. The root and rhizoma of S. miltiorrhiza Bunge (Danshen) and the rhizoma of D. nipponica Makino (Chuanshanlong) are the most important components of HQT.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that herbal medicine monotherapy or combination therapy has efficacy in relieving clinical symptoms, signs, and indicators of inflammatory activity for RA patients (12,32). According to previous pharmacological studies, the herbals in HQT formula are proven to have a variety of pharmacological effects, such as anti-inflammatory properties, analgesia, and immune suppression (33,34) fibroblast-like synoviocytes obtained from RA patients (35,36). Also, tanshinone VI, an abietane diterpene extracted from the root of S. miltiorrhiza Bunge, could improve bone loss by inhibiting osteoclastic bone resorption through inhibition of nuclear factor-κB and receptor activator of nuclear factor kappaκ ligand pathways (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have explored potential mechanisms of action (MoA) for TCMs in treating RA and other rheumatic disorders through a number of pre-clinical studies including in silico network modeling [20], in vitro cellular assays [20,21] and in vivo animal experiment [22]. Although insightful, results of these studies warrant further validation in the clinical settings.…”
Section: Introductionmentioning
confidence: 99%